Analisis Pengaruh Literasi Ekonomi dan Gaya Hidup Hedonis Terhadap Perilaku Konsumtif Mahasiswa di Era Pandemi Covid-19 - Febriana Sa’idah; Dhiah Fitrayati (Jurnal Paedagogy, 2022)
This research aims to analyze the influence of economic literacy and a hedonistic lifestyle on students' consumption behaviors during the Covid-19 pandemic. This study employed a quantitative strategy and correlation method. Students of the 2018 Economic Education Study Program of UNESA served as the population in this study, with a total sample size of 63 participants drawn via saturation sampling. The research used Likert-scaled questionnaires for data collection. The study used the Statistics Program of Social Science (SPSS) to process the data and analyze multiple literal regressions. The study showed a partial negative effect of economic literacy on consumptive behaviors. The t count (-3.406) > t table (-1.670649) showed a significance value of 0.001 < 0.05, so the conclusion of the hypothesis H0 is rejected, and Ha is accepted. This research reveals that consumptive behaviors are simultaneously influenced by economic and lifestyle literacy. Thus, students must improve their economic literacy to control their consumption appropriately. That is because the higher the economic literacy possessed, the lower the consumptive behavior of students.